The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1002/adfm.202307263
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunction‐Accelerating Lithium Salt Dissociation in Polymer Solid Electrolytes

Junbao Kang,
Nanping Deng,
Dongjie Shi
et al.

Abstract: The practical application of solid‐state lithium‐metal batteries (SSLMBs) based on polymer solid electrolytes has been hampered by their low ion conductivity and lithium‐dendrite‐induced short circuits. This study innovatively introduces 1D ferroelectric ceramic‐based Bi4Ti3O12‐BiOBr heterojunction nanofibers (BIT‐BOB HNFs) into poly(ethylene oxide) (PEO) matrix, constructing lithium‐ion conduction highways with “dissociators” and “accelerating regions.” BIT‐BOB HNFs, as 1D ceramic fillers, not only can constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Initially, the incorporation of LLZO nanofibers decreases the degree of crystallinity in the polymer matrix, hence enhancing the ionic conductivity. 27 Furthermore, the LLZO nanofibers' significant aspect ratio facilitates the creation of a rapid conduction pathway, allowing for efficient long-distance transportation of Li + . 28 It should be emphasized that, despite the similarity in ionic conductivity of the electrolyte, the variation in thickness results in a discrepancy in migration distance.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, the incorporation of LLZO nanofibers decreases the degree of crystallinity in the polymer matrix, hence enhancing the ionic conductivity. 27 Furthermore, the LLZO nanofibers' significant aspect ratio facilitates the creation of a rapid conduction pathway, allowing for efficient long-distance transportation of Li + . 28 It should be emphasized that, despite the similarity in ionic conductivity of the electrolyte, the variation in thickness results in a discrepancy in migration distance.…”
Section: Resultsmentioning
confidence: 99%
“…Comprehensive simulations and characterizations reveal the critical role of Brthiophene unit in POP, in which the unique structure design not only improve the efficiency of electron transfer, make CÀ Br easier break, but also facilitates the cleavage of CÀ F bond of TFSI À . Therefore, the dihalide LiF-LiBr were in situ [48][49][50][51][52][53][54][55][56]…”
Section: Discussionmentioning
confidence: 99%
“…[32] The weight ratio of filler was further investigated for the optimization of the ionic conductivity of the electrolyte. Figure S7 shows the EIS results of the SPE membrane under the frequency from 0.1 Hz to 1 MHz at various temperatures (30,40,50, and 60 °C). It can be found that the ionic conductivity varies linearly with temperature.…”
Section: Electrochemical and Thermal Properties Of Spesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, wearable electronic products have attracted widespread attention from researchers due to their flexible and portable characteristics, which are in line with the future development direction of intelligence. , To further improve the practicality of flexible wearable products, these intelligent fiber materials are usually endowed with certain integrated functions such as elastic modulus, mechanical strength, conductivity, thermal conductivity, biocompatibility, and breathability. Among them, coaxial heterojunction fibers with a core–shell structure are easy to integrate multiple functions, which have huge advantages in the wearable field. , At present, heterojunction fibers are mainly achieved through coaxial double-jet electrospinning technology, nanofiber interface coating modification, and other methods. However, these methods are complex and difficult to scale up, greatly limiting their further application. Therefore, the exploratory research of facile construction strategies for heterojunction fibers has important academic research significance and practical value for market applications.…”
Section: Introductionmentioning
confidence: 99%